THE POWER OF PERSPECTIVE: EDDISON WALTERS' RISK EXPECTATION THEORY AND GLOBAL FINANCE CRISIS - Smith, John (International Journal of Allied Research in Economics (IJARE), 2023)
The Global Financial Crisis of 2007 and 2008 was a major economic event that had a significant impact on the global economy. The widely held theory that the crisis was caused by a financial and real estate bubble has been challenged by recent research. Walters (2018) presented evidence that there was no statistically significant evidence of change in the growth of net FDI inflow for developed countries for periods preceding and subsequent to the crisis. This suggests that the crisis was not caused by a bubble, but by other factors, such as the Eddison Walters Risk Expectation Theory.